DEVELOPING ENGLISH INSTRUCTIONAL MATERIAL: THEORY OF EVOLUTION FOR BIOLOGY EDUCATION DEPARTMENT STUDENTS (International Conference on Social and Islamic Studies, 2021)
The research is aimed to develop English Instructional Module for Biology Education Department: Evolution at UIN Alauddin Makassar. The Research and Development model implemented in this study was 4-D Approach (Define, Design, Development, and Disseminate), but Disseminate phase is not conducted because corona pandemic. In this research involved the students of Biology Education Department, the lecturers of Biology Education Department, and 2 experts from English Education Department at UIN Alauddin Makassar. The researcher used three instruments which are Questionnaire, Interview Guideline and Evaluation Checklist. To obtain the data, the research will conduct an interview as qualitative analysis for the students and lecturers by using interview guidelines constructed based on the theory of Dudley Evans and St. John. Meanwhile, the researcher will use evaluation checklist as quantitative analysis and the module material design would validate by the expert’s judgment. The results of this research expressed that the students of Biology Education need an instructional material in context module which include integrated skills and not general module but focus on English Specific Purposes due to the students’ needs of Biology Education. The data of the students’ need became the basis in developing module. This research can be utilized both for lecturer and students as a learning source. Moreover, for further research, it could be a helpful guideline in developing a language teaching material by adapting the same model.